Studi Literatur Faktor Faktor Keputusan UMKM Tangerang dalam Memilih Ecommerce - Mahnun Masádi; Ahmad Nurhadi (LAP4B, 2025)
This study aims to provide an understanding of research related to the theme Literature Review on Factors Influencing MSME Decision-Making in Tangerang in Choosing E-commerce. It seeks to describe and explain the determinant factors associated with and influencing decision-making factors in selecting e-commerce. This research employs a literature review method to examine the locus and discussion of e-commerce selection decision factors and their determinants over the past five years (2020-2024). Data are derived from secondary sources, such as nationally indexed journals. According to Vosviewer, mapping indicates that the keyword